Download presentation

Presentation is loading. Please wait.

Published byJohnathon Ell Modified over 6 years ago

1
Factoring x2 + bx + c Warm Up Lesson Presentation Lesson Quiz

2
Warm Up 1. Which pair of factors of 8 has a sum of 9? 2. Which pair of factors of 30 has a sum of –17? Multiply. 1 and 8 –2 and –15 3. (x +2)(x +3) x2 + 5x + 6 4. (r + 5)(r – 9) r2 – 4r – 45

3
Objective Factor quadratic trinomials of the form x2 + bx + c.

4
In Chapter 7, you learned how to multiply two binomials using the Distributive Property or the FOIL method. In this lesson, you will learn how to factor a trinomial into two binominals.

5
Notice that when you multiply (x + 2)(x + 5), the constant term in the trinomial is the product of the constants in the binomials. (x + 2)(x + 5) = x2 + 7x + 10 You can use this fact to factor a trinomial into its binomial factors. Look for two numbers that are factors of the constant term in the trinomial. Write two binomials with those numbers, and then multiply to see if you are correct.

6
**Example 1A: Factoring Trinomials by Guess and Check**

Factor x2 + 15x + 36 by guess and check. ( )( ) Write two sets of parentheses. (x + )(x + ) The first term is x2, so the variable terms have a coefficient of 1. The constant term in the trinomial is 36. Try factors of 36 for the constant terms in the binomials. (x + 1)(x + 36) = x2 + 37x + 36 (x + 2)(x + 18) = x2 + 20x + 36 (x + 3)(x + 12) = x2 + 15x + 36 The factors of x2 + 15x + 36 are (x + 3)(x + 12). x2 + 15x + 36 = (x + 3)(x + 12)

7
**When you multiply two binomials, multiply:**

First terms Outer terms Inner terms Last terms Remember!

8
** Check It Out! Example 1a**

Factor each trinomial by guess and check. x2 + 10x + 24 ( )( ) Write two sets of parentheses. (x + )(x + ) The first term is x2, so the variable terms have a coefficient of 1. The constant term in the trinomial is 24. (x + 1)(x + 24) = x2 + 25x + 24 Try factors of 24 for the constant terms in the binomials. (x + 2)(x + 12) = x2 + 14x + 24 (x + 3)(x + 8) = x2 + 11x + 24 (x + 4)(x + 6) = x2 + 10x + 24 The factors of x2 + 10x + 24 are (x + 4)(x + 6). x2 + 10x + 24 = (x + 4)(x + 6)

9
** Check It Out! Example 1b**

Factor each trinomial by guess and check. x2 + 7x + 12 ( )( ) Write two sets of parentheses. (x + )(x + ) The first term is x2, so the variable terms have a coefficient of 1. The constant term in the trinomial is 12. (x + 1)(x + 12) = x2 + 13x + 12 Try factors of 12 for the constant terms in the binomials. (x + 2)(x + 6) = x2 + 8x + 12 (x + 3)(x + 4) = x2 + 7x + 12 The factors of x2 + 7x + 12 are (x + 3)(x + 4). x2 + 7x + 12 = (x + 3)(x + 4)

10
The guess and check method is usually not the most efficient method of factoring a trinomial. Look at the product of (x + 3) and (x + 4). x2 12 (x + 3)(x +4) = x2 + 7x + 12 3x 4x The coefficient of the middle term is the sum of 3 and 4. The third term is the product of 3 and 4.

12
**When c is positive, its factors have the same sign**

When c is positive, its factors have the same sign. The sign of b tells you whether the factors are positive or negative. When b is positive, the factors are positive and when b is negative, the factors are negative.

13
**Example 2A: Factoring x2 + bx + c When c is Positive**

Factor each trinomial. Check your answer. x2 + 6x + 5 (x + )(x + ) b = 6 and c = 5; look for factors of 5 whose sum is 6. Factors of 5 Sum 1 and The factors needed are 1 and 5. (x + 1)(x + 5) Check (x + 1)(x + 5) = x2 + x + 5x + 5 Use the FOIL method. = x2 + 6x + 5 The product is the original polynomial.

14
**Example 2B: Factoring x2 + bx + c When c is Positive**

Factor each trinomial. Check your answer. x2 + 6x + 9 (x + )(x + ) b = 6 and c = 9; look for factors of 9 whose sum is 6. Factors of 9 Sum 1 and 3 and The factors needed are 3 and 3. (x + 3)(x + 3) Check (x + 3)(x + 3 ) = x2 +3x + 3x + 9 Use the FOIL method. = x2 + 6x + 9 The product is the original polynomial.

15
**Example 2C: Factoring x2 + bx + c When c is Positive**

Factor each trinomial. Check your answer. x2 – 8x + 15 (x + )(x + ) b = –8 and c = 15; look for factors of 15 whose sum is –8. Factors of 15 Sum –1 and –15 –16 –3 and –5 –8 The factors needed are –3 and –5 . (x – 3)(x – 5) Check (x – 3)(x – 5 ) = x2 – 3x – 5x + 15 Use the FOIL method. = x2 – 8x + 15 The product is the original polynomial.

16
** Check It Out! Example 2a**

Factor each trinomial. Check your answer. x2 + 8x + 12 (x + )(x + ) b = 8 and c = 12; look for factors of 12 whose sum is 8. Factors of Sum 1 and 2 and The factors needed are 2 and 6 . (x + 2)(x + 6) Check (x + 2)(x + 6 ) = x2 + 2x + 6x + 12 Use the FOIL method. = x2 + 8x + 12 The product is the original polynomial.

17
** Check It Out! Example 2b**

Factor each trinomial. Check your answer. x2 – 5x + 6 (x + )(x+ ) b = –5 and c = 6; look for factors of 6 whose sum is –5. Factors of 6 Sum –1 and –6 –7 –2 and –3 –5 The factors needed are –2 and –3. (x – 2)(x – 3) Check (x – 2)(x – 3) = x2 –2x – 3x + 6 Use the FOIL method. = x2 – 5x + 6 The product is the original polynomial.

18
** Check It Out! Example 2c**

Factor each trinomial. Check your answer. x2 + 13x + 42 (x + )(x + ) b = 13 and c = 42; look for factors of 42 whose sum is 13. Factors of 42 Sum 1 and 6 and 7 13 2 and The factors needed are 6 and 7. (x + 6)(x + 7) Check (x + 6)(x + 7) = x2 + 7x + 6x + 42 Use the FOIL method. = x2 + 13x + 42 The product is the original polynomial.

19
** Check It Out! Example 2d**

Factor each trinomial. Check your answer. x2 – 13x + 40 b = –13 and c = 40; look for factors of 40 whose sum is –13. (x + )(x+ ) Factors of 40 Sum –2 and –20 –22 –4 and –10 –14 –5 and – –13 The factors needed are –5 and –8. (x – 5)(x – 8) Check (x – 5)(x – 8) = x2 – 5x – 8x + 40 Use the FOIL method. = x2 – 13x + 40 The product is the original polynomial.

20
**When c is negative, its factors have opposite signs**

When c is negative, its factors have opposite signs. The sign of b tells you which factor is positive and which is negative. The factor with the greater absolute value has the same sign as b.

21
**Example 3A: Factoring x2 + bx + c When c is Negative**

Factor each trinomial. x2 + x – 20 b = 1 and c = –20; look for factors of –20 whose sum is 1. The factor with the greater absolute value is positive. (x + )(x + ) Factors of –20 Sum –1 and –2 and –4 and The factors needed are +5 and –4. (x – 4)(x + 5)

22
**Example 3B: Factoring x2 + bx + c When c is Negative**

Factor each trinomial. x2 – 3x – 18 b = –3 and c = –18; look for factors of –18 whose sum is –3. The factor with the greater absolute value is negative. (x + )(x + ) Factors of –18 Sum 1 and – –17 2 and – – 7 3 and – – 3 The factors needed are 3 and –6. (x – 6)(x + 3)

23
If you have trouble remembering the rules for which factor is positive and which is negative, you can try all the factor pairs and check their sums. Helpful Hint

24
** Check It Out! Example 3a Factor each trinomial. Check your answer.**

x2 + 2x – 15 b = 2 and c = –15; look for factors of –15 whose sum is 2. The factor with the greater absolute value is positive. (x + )(x + ) Factors of –15 Sum –1 and –3 and The factors needed are –3 and 5. (x – 3)(x + 5)

25
** Check It Out! Example 3b Factor each trinomial. Check your answer.**

x2 – 6x + 8 (x + )(x + ) b = –6 and c = 8; look for factors of 8 whose sum is –6. Factors of 8 Sum –1 and – –7 –2 and – –6 The factors needed are –4 and –2. (x – 2)(x – 4)

26
** Check It Out! Example 3c Factor each trinomial. Check your answer.**

X2 – 8x – 20 (x + )(x + ) b = –8 and c = –20; look for factors of –20 whose sum is –8. The factor with the greater absolute value is negative. Factors of –20 Sum 1 and – –19 2 and – –8 The factors needed are –10 and 2. (x – 10)(x + 2)

27
A polynomial and the factored form of the polynomial are equivalent expressions. When you evaluate these two expressions for the same value of the variable, the results are the same.

28
**Example 4A: Evaluating Polynomials**

Factor y2 + 10y Show that the original polynomial and the factored form have the same value for n = 0, 1, 2, 3, and 4. y2 + 10y + 21 (y + )(y + ) b = 10 and c = 21; look for factors of 21 whose sum is 10. Factors of 21 Sum 1 and 3 and The factors needed are 3 and 7. (y + 3)(y + 7)

29
Example 4A Continued Evaluate the original polynomial and the factored form for n = 0, 1, 2, 3, and 4. (y + 7)(y + 3) (0 + 7)(0 + 3) = 21 (1 + 7)(1 + 3) = 32 (2 + 7)(2 + 3) = 45 (3 + 7)(3 + 3) = 60 (4 + 7)(4 + 3) = 77 y 1 2 3 4 y2 + 10y + 21 (0) + 21 = 21 y 1 2 3 4 (1) + 21 = 32 (2) + 21 = 45 (3) + 21 = 60 (4) + 21 = 77 The original polynomial and the factored form have the same value for the given values of n.

30
Check It Out! Example 4 Factor n2 – 7n Show that the original polynomial and the factored form have the same value for n = 0, 1, 2, 3, and 4. n2 – 7n + 10 (n + )(n + ) b = –7 and c = 10; look for factors of 10 whose sum is –7. Factors of 10 Sum –1 and –10 –11 –2 and –5 – 7 The factors needed are –2 and –5. (n – 5)(n – 2)

31
**Check It Out! Example 4 Continued**

Evaluate the original polynomial and the factored form for n = 0, 1, 2, 3, and 4. (n – 5)(n – 2 ) (0 – 5)(0 – 2) = 10 n 1 2 3 4 (1 – 5)(1 – 2) = 4 (2 – 5)(2 – 2) = 0 (3 – 5)(3 – 2) = –2 (4 – 5)(4 – 2) = –2 n2 –7n + 10 02 –7(0) + 10 = 10 y 1 2 3 4 32 – 7(3) + 10 = –2 22 – 7(2) + 10 = 0 42 – 7(4) + 10 = –2 12 – 7(1) + 10 = 4 The original polynomial and the factored form have the same value for the given values of n.

32
Lesson Quiz: Part I Factor each trinomial. 1. x2 – 11x + 30 2. x2 + 10x + 9 3. x2 – 6x – 27 4. x2 + 14x – 32 (x – 5)(x – 6) (x + 1)(x + 9) (x – 9)(x + 3) (x + 16)(x – 2)

33
Lesson Quiz: Part II Factor n2 + n – 6. Show that the original polynomial and the factored form have the same value for n = 0, 1, 2, 3 ,and 4. (n + 3)(n – 2)

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google